DISTRIBUTION OF ZAKAT AND GRDP PER CAPITA IN SOUTH SULAWESI - Gustang, A; Hamzah, Nasir; Hara, Muslimin K; Abdullah, Muh. Wahyuddin (Jurnal Diskursus Islam, 2021)
This study purpose to test empirically the effect of consumptive ZIS distribution on the ZIS distribution for economic activities and the provision of capital and per capita GRDP. To test the effect of ZIS distribution for economic activities and capital providing on GDP per capita. To test the effect of the consumptive ZIS distribution on the GDP per capita through the ZIS distribution for economic activities and capital providing. The type of research used is quantitative with an explanatory approach. The study population was the districts and cities in South Sulawesi. The data used are: consumptive ZIS distribution, ZIS distribution for economic activities and capital providing and GRDP per capita according to the business fields and constant prices in the form of published documents. The sample used was 105 in the form of data panels consisting of 21 districts and cities using 5 years of documentation data (2015-2019). Data processing and analysis techniques use panel data regression statistical tests and path analysis using Eviews program data processing. The results showed that:   (1) Increasing the distribution of consumptive ZIS can increase ZIS distribution for economic activities and capital providing and GRDP per capita. (2) Increasing the distribution of ZIS for economic activities and capital providing can increase GDP per capita. (3) Increasing the consumptive ZIS distribution can increase GDP per capita by increasing the ZIS distribution for economic activities and capital providing. The implication of the research results using the consumptive ZIS distribution approach model and the ZIS distribution for economic activities and the capital providing can be used as an instrument to  increase  GDP  per  capita  directly  and  indirectly.  This  implication  can  be  achieved  by encouraging an increase in the consumptive ZIS distribution and the ZIS distribution for economic activities and the provision of capital as well as public awareness of the obligation of zakat.